Effects of hormonal changes in women on skin pigmentation - Kubia, Marlena; Rotsztejn, Helena (Menopause Review/Przegląd Menopauzalny, 2012)
The structure, function and appearance of the skin are a result of numerous endogenic and exogenic factors which change throughout life. The hormonal condition makes it possible to distinguish particular phases of a woman’s life, which are associated with her biological age and of which certain physiological conditions and diseases of the skin are characteristic. Hormonal regulation affects, among other things, the process of melanogenesis which becomes more intense under the influence of sex hormones. It manifests in the skin by hyperpigmentation during pregnancy, when using hormonal contraception or during hormone replacement therapy at menopause.